A Novel Technique for Anterior Vaginal Wall Prolapse Repair: Anterior Vaginal Wall Darn. (21st January 2013) - Köse, Osman; Sağlam, Hasan S.; Kumsar, Şükrü; Budak, Salih; Adsan, Öztuğ
Abstract : Aim . The aim of this study is to introduce a new technique, anterior vaginal wall darn (AVWD), which has not been used before to repair the anterior vaginal wall prolapse, a common problem among women. Materials and Methods . Forty-five women suffering from anterior vaginal wall prolapse were operated on with a new technique. The anterior vaginal wall was detached by sharp and blunt dissection via an incision beginning from the 1 cm proximal aspect of the external meatus extending to the vaginal apex, and the space between the tissues that attach the lateral walls of the vagina to the arcus tendineus fascia pelvis (ATFP) was then darned. Preoperation and early postoperation evaluations of the patients were conducted and summarized. Results . Data were collected six months after operation. Cough stress test (CST), Pelvic Organ Prolapse Quantification (POP-Q) evaluation, Incontinence Impact Questionnaire (IIQ-7), and Urogenital Distress Inventory (UDI-6) scores indicated recovery. According to the early postoperation results, all patients were satisfied with the operation. No vaginal mucosal erosion or any other complications were detected. Conclusion . In this initial series, our short-term results suggested that patients with grade II-III anterior vaginal wall prolapsus might be treated successfully with the AVWD method.